Access to Justice for Indigenous Communities under the Inter-American Human Rights System - Garcia Moctezuma, Hector Zahid; Ascencio López, Noemi (Scientific journal of social studies, 2026)
The objective of the article is to analyze Indigenous peoples’ access to justice within the framework of the Inter-American Human Rights System, in order to identify normative advances and persistent obstacles that define its effectiveness. The analytical-synthetic method and documentary review of international instruments and Inter-American jurisprudence were used to examine the evolution of protective standards from the perspective of legal pluralism and interculturality. The study argues that the IAHRS has contributed positively to making visible the collective dimension of access to justice and to consolidating criteria regarding prior consultation, collective property, and the recognition of Indigenous normative systems. Nevertheless, a gap is observed between formal recognition and effective implementation within States, evidenced by linguistic barriers, institutional weakness, and lack of coordination between jurisdictions. It is concluded that the main challenge lies in insufficient state will to materialize Inter-American standards; therefore, institutional reforms, intercultural training, and effective compliance mechanisms are required to ensure truly inclusive access to justice.
Keywords: Access to justice; Indigenous communities; legal pluralism; Inter-American Human Rights System